1997
DOI: 10.3177/jnsv.43.155
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Sunflower and Olive Oil Diets Affect Serum Lipid Levels in Steatotic Rat Liver Differently.

Abstract: SummaryThis work describes the long-term effects of two different diets, one rich in olive oil and the other in sunflower oil, on serum lipid and lipoprotein levels after the establishment of fatty liver in rats 8 and 15 months old. The serum lipid and lipoprotein levels as well as the steatotic process have been evaluated by biochemical and histological methods, respectively. The results showed that fatty liver was well developed with both long-term high-fat diets, and hepatocytes were filled with many lipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
2
19
0
1
Order By: Relevance
“…This notion is derived mainly from cohort studies demonstrating the positive impact of the so-called Mediterranean diet on cardiovascular morbidity and mortality (Kris-Etherton 1999). Consistent with our results, previous animal studies have found insulin resistance and elevations of plasma lipids in rats fed high-fat diets based on olive oil (Del Moral et al 1997, Storlien et al 1991, Tsunoda et al 1998. The evidence of specific positive effects of monounsaturated fats on glucose and lipid metabolism is not very conclusive.…”
Section: Discussionsupporting
confidence: 67%
“…This notion is derived mainly from cohort studies demonstrating the positive impact of the so-called Mediterranean diet on cardiovascular morbidity and mortality (Kris-Etherton 1999). Consistent with our results, previous animal studies have found insulin resistance and elevations of plasma lipids in rats fed high-fat diets based on olive oil (Del Moral et al 1997, Storlien et al 1991, Tsunoda et al 1998. The evidence of specific positive effects of monounsaturated fats on glucose and lipid metabolism is not very conclusive.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, it is well-known that the type of fat in the diet affects serum lipids and lipoprotein levels, as well as liver morphology and biochemical parameters (8) , and the influence of dietary fat composition on serum lipids and hepatic fibrosis is receiving much attention (9,10). Thus, we have shown that different dietary fats affect serum lipid levels in hepatical steatosis (8).…”
mentioning
confidence: 74%
“…High-fat diets (fat content 14%), semi-purified and balanced , were prepared as previously described (8). The standard (control) diet was a commercially available rat feed (fat content 4-5%).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations